2018
DOI: 10.1021/acs.bioconjchem.7b00726
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Imaging of Prostate Cancer with Ga-68-Labeled Gastrin-Releasing Peptide Receptor Agonist BBN7–14 and Antagonist RM26

Abstract: Radiolabeled bombesin (BBN) analogs have long been used for developing gastrin-releasing peptide receptor (GRPR) targeted imaging probes, and tracers with excellent in vivo performance including high tumor uptake, high contrast, and favorable pharmacokinetics are highly desired. In this study, we compared the 68Ga-labeled GRPR agonist (Gln–Trp–Ala–Val–Gly–His–Leu–Met–NH2, BBN7–14) and antagonist (d-Phe–Gln–Trp–Ala–Val–Gly–His–Sta–Leu–NH2, RM26) for the positron emission tomography (PET) imaging of prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Examination of the structure-activity profile of this fragment has revealed numerous highly GRPR-binding derivatives with different pharmacologic profiles in terms of agonistic versus antagonistic character (4)(5)(6). Exceptional work by Maecke's group and others has identified antagonistic analogs (e.g., RM26) that have substantially higher tumor uptake and better nontarget clearance profiles than agonistic analogs (7)(8)(9). Despite encouraging clinical and preclinical results (10,11), the relatively short tumor residence time of low-molecular-weight constructs such as GRPR-targeted peptides still represents a translational hurdle, particularly with regard to radiotherapeutic uses (12).…”
mentioning
confidence: 99%
“…Examination of the structure-activity profile of this fragment has revealed numerous highly GRPR-binding derivatives with different pharmacologic profiles in terms of agonistic versus antagonistic character (4)(5)(6). Exceptional work by Maecke's group and others has identified antagonistic analogs (e.g., RM26) that have substantially higher tumor uptake and better nontarget clearance profiles than agonistic analogs (7)(8)(9). Despite encouraging clinical and preclinical results (10,11), the relatively short tumor residence time of low-molecular-weight constructs such as GRPR-targeted peptides still represents a translational hurdle, particularly with regard to radiotherapeutic uses (12).…”
mentioning
confidence: 99%
“…Generally, GPCR peptide antagonists are poorly and slowly internalized, if at all, whereas agonists are extensively and rapidly internalized (Mantey et al, 1993;Ginj et al, 2006;Moreno et al, 2016;Dalm et al, 2017). The above generalization is also true for BnRs, where numerous studies have reported that most BnR peptide antagonists are poorly internalized, if at all (Mantey et al, 1993;Cescato et al, 2008;Varasteh et al, 2013;Nock et al, 2017;Popp et al, 2017;Cheng et al, 2018). The internalization of radiolabeled Bantag-1 in our studies was not due to the possibility that Bantag-1 was functioning as a partial agonist, because in previous studies it has been reported to have no agonist activity at the BRS-3 receptor for the activation of phospholipase C, as assessed by either stimulation of the generation of phosphoinositides (Moreno et al, 2013) or mobilization of cellular calcium (Guan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have demonstrated that a number of common neoplasms overexpress BnRs (i.e., prostate, breast, lung, pancreas, and CNS tumors) (Reubi et al, 2002;Reubi, 2013;Moreno et al, 2016), and in some tumors such as lung cancers, BRS-3 is the most frequently overexpressed and is expressed in the highest numbers (Moreno et al, 2018). A number of recent studies report the ability of BnR radioligands to image various human tumors in humans, particularly breast and prostate, using high-affinity GRPR ligands (Sancho et al, 2011;Moreno et al, 2016;Ferreira et al, 2017;Cheng et al, 2018;Zang et al, 2018), and with the high expression of BRS-3 in lung tumors (Moreno et al, 2018) a similar approach might be used with radiolabeled Bantag-1. Furthermore, using 177 Lu-or 90 Y-labeled peptides, peptide-radioreceptor therapy has been shown to be effective and has been recently approved for the treatment of neuroendocrine tumors with radiolabeled somatostatin receptor ligands (Strosberg et al, 2016;Ito and Jensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the localization of 68 Ga‐SB3 in a small number of therapy‐naïve prostate cancer patients could be well correlated with GRPR‐expression levels in the lesions, determined by receptor autoradiography on patient biopsy samples . We and others have previously compared GRPR‐radioantagonist and GRPR‐radioagonist pairs . However, selection of individual analogs for comparison in these studies has not taken into account important structural differences at the N‐terminus of peptide conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…21 We and others have previously compared GRPR-radioantagonist and GRPR-radioagonist pairs. 19,[22][23][24][25] However, selection of individual analogs for comparison in these studies has not taken into account important structural differences at the N-terminus of peptide conjugates. Hence, the observed response differences could not be attributed exclusively to agonism/ antagonism at the GRPR.…”
Section: Introductionmentioning
confidence: 99%